2001
DOI: 10.1111/j.1471-0528.2001.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Fever in labour and neonatal encephalopathy: a prospective cohort study

Abstract: Objective To determine whether the reported association of maternal fever with neonatal encephalopathy is independent of other associated intrapartum risk factors.Design Prospective cohort study.Setting Dublin teaching hospital delivery ward. Population 4915 low risk women in labour at 36-41 weeks of gestation.Methods Using logistic regression with odds ratios and 95% con®dence intervals, the incidence of neonatal encephalopathy and other neonatal outcomes of women who had an intrapartum fever .37.58 C was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 23 publications
2
20
1
Order By: Relevance
“…Perinatal brain injury often results in severe and long-lasting disabilities, like motor deficits, seizures and severe cognitive, psychological and behavioral problems, which represent an enormous burden for the child, its parents and society [1,2,3]. Importantly, the risk of developing neonatal encephalopathy is strongly increased after maternal intrapartum fever or other antenatal inflammatory conditions like chorioamnionitis [4,5,6,7]. Moreover, it is known that exposure of the fetal brain to a proinflammatory environment in utero negatively influences clinical outcome after asphyxia, including an increased risk of development of spastic cerebral palsy [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Perinatal brain injury often results in severe and long-lasting disabilities, like motor deficits, seizures and severe cognitive, psychological and behavioral problems, which represent an enormous burden for the child, its parents and society [1,2,3]. Importantly, the risk of developing neonatal encephalopathy is strongly increased after maternal intrapartum fever or other antenatal inflammatory conditions like chorioamnionitis [4,5,6,7]. Moreover, it is known that exposure of the fetal brain to a proinflammatory environment in utero negatively influences clinical outcome after asphyxia, including an increased risk of development of spastic cerebral palsy [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Results of the present study suggest that antioxidant strategies may be effective in PICH prevention, especially because lobar location of PICH brings a higher risk of recurrence [23]. Thus, diet with selenium-containing food (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These adverse outcomes have been shown to affect primarily the respiratory [16] and neurologic systems [17,18] of the newborn, with one study showing intrapartum fever as a strong predictor of infection-related early neonatal death in term pregnancies (OR 3.16, 95% CI: 1.56, 6.40) [1]. Impey et al [17,18] demonstrated that intrapartum fever is associated with an almost 5-fold risk for neonatal encephalopathy and a 3.4-fold increase in the risk of unexplained neonatal seizures [17]. In a small retrospective study, neonates of febrile parturients had increased risk of low Apgar scores, seizures, hypotonia, and need for assisted ventilation [11].…”
Section: Discussionmentioning
confidence: 99%